Modifying tradition: Understanding organizational change in Chinese elite sport training at the grassroots level. - Ma, Y.; Kurscheidt, M. (Sustainability, 2021)
This research examines the organizational change in Chinese elite sport training at the grassroots level, which is perceived as foundational to and crucial for the development of sustainable competitive advantage at the Olympics. Predicted on an in-depth single case study design linked to qualitative research, this study pursued a "thick description" of the process of change in Shanghai elite sport training by identifying the impetus for change and factors moderating the change process. All qualitative data were sourced from semi-structured interviews and official and semi-official documents. Participants included current sport leaders; officials/administrators; senior, including head and non-head, coaches; and renowned Chinese social science scholars who either specialize inor are familiar with the elite sport training scene in general and the landscape at the grassroots level.The key findings, on the basis of organizational change theory, were that the internal and external political pressures are strongly linked to the growing concern about athlete performance management,the alignment of elite sport training with the sport service industry, and limited financial resources;the functional pressures emerge from the broadening of the talent pool of money-consuming sportsand newly added Olympic sports; and other fields` successful practices, the unlimited registration rule, and a virtuous cycle of training contribute to organizational change.